Radiological assessment of experimental mono-segmental posterior-lateral lumbar fusion using autologous platelet rich fibrin - Radchenko, Volodymyr; Palkin, Alexandr; Kolesnichenko, Vera (ORTHOPAEDICS TRAUMATOLOGY and PROSTHETICS, 2017)
The results of the use of autologous platelet-rich fibrin, for posterolateral lumbar spinal fusion are discussed. Objective: to evaluate the radiographic signs of experimental posterolateral lumbar spine fusion using fibrin-rich platelets. Methods: mono segmental posterolateral lumbar spinal fusion performed in 42 adult male California rabbits aged 4–5 months, which were divided into 6 groups of 7 animals each. In the control group 1 grafts were not used in group 2 used the local autograft, group 3 — local autograft combined with fibrin-rich platelets, 4 — allograft of ilium, 5 — allograft from ilium combined with fibrin-rich platelets, 6 — fibrin-rich platelets. Results: revealed radiographic characteristics of posterolateral osteoplastic fusion, namely the formation of continuous trabecular bone in the area of spinal fusion, preserved height of interbody gaps, homogenous structure of newly formed bone, increasing the intensity of X-ray images in fusion masses. In radiometric studies identified more intensive bone density block of rabbits in groups 3 and 5, as well as forming a homogeneous bone accretion in group 6. <span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: 'Times New Roman'; mso-fareast-font-family: 'Times New Roman'; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA;">Conclusions:<span style="font-size: 14.0pt; mso-bidi-font-size: 9.0pt; font-family: 'Times New Roman'; mso-fareast-font-family: 'Times New Roman'; color: #221e1f; mso-ansi-language: RU; mso-fareast-language: RU; mso-bidi-language: AR-SA; mso-bidi-font-style: italic;"> groups of rabbits with osteoplastic spinal fusion detected radiographic signs of bone formed block in 77.1 % of cases in the control decortication group of transverse processes — in 57.1 %. Results of roentgenometric zone fusion evaluation suggest that autologous platelet rich fibrin, promotes strong bone accretion.